Antibacterial Activity of Organic Acids on the Growth of Selected Bacteria in Meat Samples - Raftari, Mohammad (2009)
Meat can harbour a large variety of pathogenic and spoilage microorganisms which include mesophilic and psychrophilic bacteria, during slaughtering and further processing. These microorganisms may be sources of infection to human and spoilage of meat. Organic acids are generally recognized as safe antimicrobial agents and the low dilute solutions of organic acids are generally without affecting on the desirable sensory properties of meat; in addition, they do not create residual problems when used as carcass decontaminants. Spray wash treatments utilizing three concentrations (1, 1.5 and 2%) of acetic, lactic, propionic and formic acids (individually and/or in combination of two acids) were performed to evaluate their efficacy in reducing numbers of Escherichia coli O157:H7, Staphylococcus aureus, Listeria monocytogenes, Salmonella Typhimurium and Pseudomonas putida on meat tissues stored at 4±1ºC. The procured beef pieces were decontaminated with hot water and then inoculated with E. coli O157:H7, S. aureus, L. monocytogenes, S. Typhimurium and P. putida seperately which then were spray washed with organic acids for 15 seconds either individually or in combination of two acids separately. The population of E. coli O157:H7, S. Typhimurium, S. aureus, L. monocytogenes and P. putida (P<0.05) were reduced statistically after being spray washed with all treatments at a range of 0.89-3.19 log10 cfu/ml. The inhibitory effect of all organic acids according to the concentration was 2% concentration > 1.5% concentration > 1% concentration. Mean log reductions of E. coli O157:H7, S. Typhimurium, S. aureus, L. monocytogenes and P. putida showed that the antibacterial effect of formic acid > lactic acid > acetic acid > propionic acid. Combinations of two organic acids indicated a stronger inhibitory effect on selected bacteria compared to the effect of each acid alone. The combinations of acetic and formic, lactic and formic, and propionic and formic acids showed higher reductions effect at ranges of 0.22-1.67, 0.26-1.55, 1.43-1.56, 1.43-1.69 and 0.44-1.59 log10 cfu/ml for E. coli O157:H7, S. Typhimurium, S. aureus, L. monocytogenes and P. putida respectively, more than combinations of acetic and lactic, acetic and propionic, and lactic and propionic acids. The combination of lactic and formic acids showed the highest reduction effect, where more than 3 log10 cfu/ml, of all bacterial species were reduced. The populations of S. aureus and L. monocytogenes as Gram-positive bacteria reduced more significantly (P<0.05) than the population of E. coli O157:H7, S. Typhimurium and P. putida as Gram-negative bacteria. The results of this study indicated that formic acid is a good antibacterial agent for decontaminating animals’ carcass surfaces especially when mixed with lactic acid.